Whole-Ecosystem Warming Increases Plant-Available Nitrogen and Phosphorus in an Ombrotrophic Bog - Colleen M. Iversen; John Latimer; Deanne J. Brice; Joanne Childs; Holly M. Vander Stel; Camille E. Defrenne; Jake Graham; Natalie A. Griffiths; Avni Malhotra; Richard J. Norby; Keith C. Oleheiser; Jana R. Phillips; et al. (Ecosystems, 2023)

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Combined orbits and clocks from IGS second reprocessing - Jake Griffiths (Journal of Geodesy, 2019)

Evaluation of GPS orbit prediction strategies for the IGS Ultra-rapid products - Kevin K. Choi; Jim Ray; Jake Griffiths; Tae-Suk Bae (GPS Solutions, 2013)

Agricultural land use alters the seasonality and magnitude of stream metabolism - Natalie A. Griffiths; Jennifer L. Tank; Todd V. Royer; Sarah S. Roley; Emma J. Rosi-Marshall; Matt R. Whiles; Jake J. Beaulieu; Laura T. Johnson (Limnology and Oceanography, 2013)
We present a comprehensive data set of gross primary production (GPP) and ecosystem respiration (ER) in open‐canopy, nutrient‐rich streams draining row‐crop agriculture in the midwestern United States. We used two approaches to characterize temporal and spatial variation in whole‐stream metabolism: continuous measurements in one agricultural stream for 1 yr, and periodic daily measurements in six agricultural streams on six dates spanning summer, autumn, and winter. Continuous measurements revealed high rates of GPP (range: 0.1 to 22.0 g O 2 m −2 d −1 ) and ER (range: −0.9 to −34.8 g O 2 m −2 d −1 ) that varied seasonally with light availability and temperature. GPP and ER were correlated during periods of high autotrophic production, suggesting that autotrophic respiration comprised a large portion of ER; however, the GPP : ER ratio exceeded 1 for only 4% of the year. While there were distinct temporal patterns in metabolism in one agricultural stream, rates of GPP and ER were similar among six streams when assessed via periodic daily measurements, and 26% of all periodic daily measurements were autotrophic with GPP : ER > 1. However, these periodic measurements were collected under baseflow conditions and may have overestimated the extent of autotrophy in agricultural streams. Overall, the open canopy and elevated nutrients of agricultural streams resulted in higher rates of GPP and ER compared with more pristine systems. Estimates of metabolism are needed from underrepresented systems to accurately quantify carbon fluxes from fluvial ecosystems.

Global GPS data analysis at the National Geodetic Survey - William G. Kass; Robert L. Dulaney; Jake Griffiths; Stephen Hilla; Jim Ray; James Rohde (Journal of Geodesy, 2009)

On the precision and accuracy of IGS orbits - Jake Griffiths; Jim R. Ray (Journal of Geodesy, 2009)